Excellent Selectivity with High Conversion in the Semihydrogenation of Alkynes using Palladium-Based Bimetallic Catalysts - Liu, Jian; Zhu, Y.; Liu, C.; Wang, X.; Cao, C.; Song, W. (WILEY-V C H VERLAG GMBH, 2017)
© 2017 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim. A series of active-carbon-supported PdPb and PdCu bimetal catalysts were prepared for the selective semihydrogenation of alkynes in the liquid phase. The Pd0.33Pb0.67/C catalyst showed the best performance for various alkynes under mild reaction conditions (room temperature and ambient H2pressure) and achieved 100 % conversion with 98 % selectivity to alkenes. In particular, over-hydrogenation was avoided at complete alkyne conversion.